Secure communication design for multi‐user peer‐to‐peer wireless relay networks. Issue 7 (1st May 2016) - Gong, Xiangwu; Long, Hang; Dong, Feihong; Yin, Hao
Abstract : In this study, physical layer security techniques are studied for multi‐user peer‐to‐peer relay networks using amplify‐and‐forward protocol in the presence of an eavesdropper. Two system designs are considered: the minimum achievable secrecy rate maximisation and the total transmit power minimisation. First, considering user fairness, the authors study the max–min achievable secrecy rate problem subject to a total transmit power constraint. Mathematically, the optimisation problem is non‐linear and non‐convex. They propose a polynomial time algorithm based on the bisection technique to solve it. Second, they study the total transmit power minimisation problem which aims at minimising the total transmit power at relays such that individual secrecy rate for each user is satisfied. The total power optimisation problem is also non‐convex, so they use the relaxation technique to transform it into a convex problem which can be efficiently solved by the gradient‐based algorithms. Numerical evaluation of the obtained secrecy rate and transmit power results shows that the proposed designs can significantly improve the performance of secure wireless communications.